Suitability of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration versus Paired Transbronchial Biopsy Specimens for Evaluating Programmed Death Ligand-1 Expression in Stage III and IV Lung Cancer: A Comparative Retrospective Study - Matsuoka, Hiroki (J Cancer, 2021)
Objectives: Cancer cells usually escape tumor-reactive T-cell responses using immune checkpoint proteins, such as programmed death protein-1 (PD-1) and its ligand, programmed death ligand-1 (PD-L1). These proteins can be blocked by immune checkpoint inhibitors (ICIs); the decision on ICI-based first-line treatment for advanced lung cancers depends on the PD-L1 levels in tumor specimens. Determining the PD-L1 expression conventionally requires histological specimens from resected tumors and core biopsy specimens. Non-small cell lung cancer (NSCLC) is usually diagnosed at stage III or IV; therefore, only small biopsy specimens, such as those obtained via endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) are available. However, the suitability of EBUS-TBNA specimens determining the PD-L1 expression levels in advanced lung cancers remains unclear. Materials and Methods: Here, we investigated the concordance rate of PD-L1 expression between EBUS-TBNA and matched transbronchial biopsy (TBB) specimens. Using the 22C3 anti-PD-L1 antibody (immunohistochemistry), we determined the PD-L1 expression levels in paired specimens obtained from 69 patients (50 with advanced NSCLC and 19 with small cell lung cancer [SCLC]), as well as the efficacy of ICIs in these patients. Results: The concordance rate of PD-L1 expression between the EBUS-TBNA and TBB specimens was 78.3%. The κ values referent to the PD-L1-positive expression rate between EBUS-TBNA and TBB specimens were 0.707 and 0.676 at cutoff limits of ≥1% and ≥50%, respectively. Among the 19 SCLC patients, 16 (84.2%) exhibited no PD-L1 expression in both EBUS-TBNA and TBB specimens. Notably, the progression-free survival of patients with ≥50% PD-L1 expression in the paired specimens who received ICI treatment was 8.3 months. Conclusion: Collectively, our results validate the use of EBUS-TBNA specimens for the determination of the PD-L1 expression levels in the context of NSCLC and SCLC.